The Effect of Brand Image, Word of Mouth, and Price Perception on Repurchase Intention in Vaseline Hand and Body Lotion at Mellebee Beauty Be Leora Jombang City - Afika Qothrunnada; Supriyono (Indonesian Journal of Business Analytics, 2024)
The purpose of this study was to determine how brand image, word-of-mouth, and price perception affected consumers' intentions to repurchase Vaseline body lotion at Mellebee Beauty in Jombang City.  In this study, quantitative research methodologies were applied. In order to collect data, 84 participants were given questionnaires utilizing purposive sampling approaches combined with non-probability selection methods. After that, the data was examined using partial least square (PLS SEM) software and variance-based structural equation modeling (SEM), sometimes known as substitute SEM methods. The study's findings indicate that Mellebee Beauty customers are inclined to repurchase Vaseline body lotion. Word-of-mouth, price perception, and brand image all have a favorable and significant impact on Be Leora Jombang.